The Influence of Low Intensity-High Intensity Plyometric Training and Hand-Eye Coordination on Jump Shoot Ability in Basketball Players of Bhinneka Solo Club: Randomized Control Trial - Putra Hadi; Muchsin Doewes; Slamet Riyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Various studies have been carried out to improve jump shoot ability of basketball, both by simple exercises and modifications to the form of training. The purpose of this study is to determine the influence of low intensity-high intensity plyometric training and hand-eye coordination on jump shoot ability. This study was conducted on basketball players of Bhinneka Solo club. The method used in this study was an experimental method with a 2 x 2 factorial design. The sample size in this study was 40 players obtained through purposive sampling. Data analysis techniques in this study used ANOVA, Saphiro Wilk test (Lilliefors test with α = 0.05) and homogeneity variance test (Leve's test with α = 0.05). The results show that (1) high intensity plyometric training has a significant influence on jump shoot basketball ability compared to low intensity plyometric training, (2) high hand-eye coordination has a significant influence on jump shoot basketball ability compared to low hand-eye coordination, (3) there is an interaction between low intensity and high intensity plyometric training and hand-eye coordination to jump shoot basketball ability.